2017
DOI: 10.2217/pgs-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the MTHFR C677T Polymorphism in Methotrexate-Induced Toxicity in Pediatric Osteosarcoma Patients

Abstract: The MTHFR C667T polymorphism is not predictive for toxicity or overall survival, but could be used for relapse risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…However, differential outcome was observed among patients receiving even the same therapeutic protocol. In previous studies, genetic polymorphisms have been shown to indicate patients’ response to chemotherapeutic agents which eventually could influence the final survival [10] , [11] , [12] , [13] . Herein, integration of such predictive genetic markers is crucial to optimize risk stratification and personalize chemotherapy strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, differential outcome was observed among patients receiving even the same therapeutic protocol. In previous studies, genetic polymorphisms have been shown to indicate patients’ response to chemotherapeutic agents which eventually could influence the final survival [10] , [11] , [12] , [13] . Herein, integration of such predictive genetic markers is crucial to optimize risk stratification and personalize chemotherapy strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of ERCC1 were reported to play important roles in the response to cisplatin mediated by the DNA repair pathway [10] . MTHFR C677T polymorphism was identified as a predictor of MTX toxicity in osteosarcoma patients [11] . The SNPs of ABCB1 and ABCC3 were found significantly associated with pharmacokinetic parameters and the occurrence of MTX toxicity [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…These SNPs might be associated with decreased activity of methylenetetrahydrofolate reductase, elevated plasma homocysteine levels, and altered distribution of folate [ 41 ]. Thus patients with this genotype were more vulnerable to potential MTX induced toxicity since these reactions above may lead to slower folate metabolism and slower cell repair [ 42 ]. Weisman et al used univariate logistic regression to reveal that the MTHFR C677T also increases the occurrence of side effects in central nervous system, manifested as headache and lethargy [ 43 ].…”
Section: The Pharmacogenetics Of Mtxmentioning
confidence: 99%
“…Weisman et al used univariate logistic regression to reveal that the MTHFR C677T also increases the occurrence of side effects in central nervous system, manifested as headache and lethargy [ 43 ]. However, Lambrecht et al argued that MTHFR C667T was not a predictive factor for toxicity [ 42 ]. Berkani et al found no association between A1298C polymorphism and MTX toxicity [ 44 ].…”
Section: The Pharmacogenetics Of Mtxmentioning
confidence: 99%
“…Therefore, one needs to be precautious with direct generalization of pharmacogenetic associations found in other malignancies or other low dose MTX-treated traits such as autoimmune diseases to osteosarcoma. In osteosarcoma, only candidate gene studies have been performed to identify relevant pharmacogenetic variants, resulting in the identification of statistically significantly associations between variants in MTHFR , MTR and ABCB1 , and MTX pharmacokinetics, toxicities and survival rates ( Patino-Garcia et al., 2009 ; Windsor et al., 2012 ; Jabeen et al., 2015 ; Park and Shin, 2016 ; Lambrecht et al., 2017 ). Previously, our group investigated the role of a genetic variant in MTHFR (rs1801133) in MTX-induced liver toxicity in patients with osteosarcoma and ALL ( Hagleitner et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%